Investigation of the effects of starch on the physical and rheological properties of bituminous binders - Erkus, Yunus; Kok, Baha; Yetkin, Zulfu (Gazi Univ, Fac Engineering Architecture, 2025)
In this study, the effect of wheat starch (WS), corn starch (CS), and potato starch (PT) on the physical and rheological properties of bitumen was investigated. The performance of starch-modified binders was compared with that of styrene-butadiene-styrene (SBS)-modified binders. Penetration, softening point, rotational viscometer, dynamic shear rheometer (DSR), multi-stress creep-elastic recovery (MSCR), beam bending rheometer (BBR), and storage stability tests were applied to both pure and modified binders. Starch reduces the penetration value of pure bitumen while increasing its softening point and viscosity values. The rutting resistance of starch-modified binders has improved. A binder modified with 30% corn starch showed higher rutting resistance than a binder modified with 3% SBS. Especially under high stress conditions, starch-modified binders have shown similar performance to SBS-modified binders. Additives have increased the low-temperature stiffness of the pure binder. Based on the results of DSR and MSCR tests, 30% starch-modified binders were classified in the same group as 3% SBS-modified binders in traffic classification. Despite the high starch content (30%), it provided better storage stability values than SBS. Starch, with its low cost, low modification temperature, availability through local resources, and performance, can be used as an alternative to synthetic polymers like SBS in bitumen modification.
Nişastanın bitümlü bağlayıcıların fiziksel ve reolojik özellikleri üzerindeki etkilerinin araştırılması
Keywords: Bitumen; modification; starch; SBS; rheological properties